Does the electric vehicle industry help achieve sustainable development goals?—evidence from China - Lu, Peiyao; Hamori, Shigeyuki; Sun, Li; Tian, Shuairu (Frontiers in Environmental Science, 2024)
Electric vehicles (EVs) are regarded as a key low-carbon technology to address sustainability challenges like climate change and air pollution. However, the real-world environmental impacts resulting from rapid EV adoption remain uncertain. This study develops a theoretical framework to quantify the impacts of EV adoption on energy consumption, carbon emissions, and air quality. Then we empirically investigates the influence of surging EV uptake in China using provincial panel data from 2015-2020. Our results indicate that increased EV stocks significantly reduced gasoline consumption but boosted coal-based power demand, shifting emissions and air pollutants from transportation to the electricity sector rather than yielding absolute reductions. We find important regional heterogeneity based on differences in grid generation profiles. In provinces more reliant on coal power, the environmental impacts were more severe. The findings also reveal a spatial spillover effect, with emissions transferred from net power-importing regions to exporters. Overall, the rapid EV transition alone appears insufficient to guarantee emissions cuts and environmental gains. Complementary efforts across sectors are essential to align industrial promotion with sustainability objectives. The empirical evidence informs integrated policy design and metrics to maximize decarbonization as EVs are deployed globally. Future research can build on this study by expanding geographical scope, incorporating projections, adopting a multi-disciplinary lens, leveraging microdata, and applying cutting-edge analytical techniques. Pursuing these directions will further advance knowledge on sustainable EV transitions.